2014
DOI: 10.1039/c4ra11524d
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell response to UV-photofunctionalized TiO2coated CoCrMo

Abstract: UV photofunctionalization of TiO2 coated implant surfaces enhanced markers of cell adhesion. This may prove to be advantageous for orthopaedic implants by supporting the colonisation and adhesion of cells capable of facilitating in bone healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…These supplements trigger the MSCs to differentiate along their osteogenic linage to form osteoblasts and as a consequence can reduce proliferation. 19,34 Cell attachment was analyzed after 24 h in GM. It was found that significantly more cells had attached to SMO and AE compared to SLA50 and SLA250 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These supplements trigger the MSCs to differentiate along their osteogenic linage to form osteoblasts and as a consequence can reduce proliferation. 19,34 Cell attachment was analyzed after 24 h in GM. It was found that significantly more cells had attached to SMO and AE compared to SLA50 and SLA250 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Discs formed of CoCrMo (Cr 26–30%, Mo 5–7%), dimensions of Ø 15 mm, 1 mm thickness, were supplied with a machined finish which was removed as previously described to create a smooth (SMO) topography . SMO discs were then used to engineer three other topographies; acid etched (AE), sand blasted acid etched using 50 µm Al 2 O 3 grit (SLA50), and sand blasted acid etched using 250 µm Al 2 O 3 (SLA250).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…collagen type I. Furthermore, surface hydrophilicity enhances cell interaction and adhesion to dental implants (Zhao et al, 2005, Logan et al, 2014a). …”
Section: Introductionmentioning
confidence: 99%